2009
DOI: 10.1074/jbc.m806470200
|View full text |Cite
|
Sign up to set email alerts
|

SNAT2 Amino Acid Transporter Is Regulated by Amino Acids of the SLC6 γ-Aminobutyric Acid Transporter Subfamily in Neocortical Neurons and May Play No Role in Delivering Glutamine for Glutamatergic Transmission

Abstract: System A transporters SNAT1 and SNAT2 mediate uptake of neutral ␣-amino acids (e.g. glutamine, alanine, and proline) and are expressed in central neurons. We tested the hypothesis that SNAT2 is required to support neurotransmitter glutamate synthesis by examining spontaneous excitatory activity after inducing or repressing SNAT2 expression for prolonged periods. We stimulated de novo synthesis of SNAT2 mRNA and increased SNAT2 mRNA stability and total SNAT2 protein and functional activity, whereas SNAT1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 98 publications
(116 reference statements)
5
31
0
Order By: Relevance
“…qPCR showed that the SNAT1 transcript level in Mecp2Ϫ/y microglia was 148 Ϯ 0.07% (n ϭ 5, p Ͻ 0.001) of that in Mecp2ϩ/y microglia. Western blot of primary microglia samples showed a cluster of SNAT1-immunoreactive bands centered ϳ55 kDa, consistent with published data (Varoqui et al, 2000;Grewal et al, 2009). SNAT1 protein levels were approximately three times more abundant in Mecp2Ϫ/y than in Mecp2ϩ/y microglia ( Fig.…”
Section: Mecp2 Deficiency In Microglia Causes Overexpression Of Glutasupporting
confidence: 80%
See 1 more Smart Citation
“…qPCR showed that the SNAT1 transcript level in Mecp2Ϫ/y microglia was 148 Ϯ 0.07% (n ϭ 5, p Ͻ 0.001) of that in Mecp2ϩ/y microglia. Western blot of primary microglia samples showed a cluster of SNAT1-immunoreactive bands centered ϳ55 kDa, consistent with published data (Varoqui et al, 2000;Grewal et al, 2009). SNAT1 protein levels were approximately three times more abundant in Mecp2Ϫ/y than in Mecp2ϩ/y microglia ( Fig.…”
Section: Mecp2 Deficiency In Microglia Causes Overexpression Of Glutasupporting
confidence: 80%
“…The following primary antibodies (dilutions) were used: anti-MeCP2 (1: 1000; Millipore), anti-NDUFA7 (1:1000; Abcam), anti-mitofilin (1: 1000; Affinity Bioreagents), anti-GAPDH (1:3000; Millipore), and anti-␤-actin (1:1000; Abcam). The well characterized, highly specific polyclonal anti-SNAT1 was described previously (Varoqui et al, 2000;Grewal et al, 2009) and was used in 1:1000 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that C/EBPβ is a neuronal activity-dependent gene. As it will be discussed later, C/EBPβ is pleiotropic in neurons and the observations that neuronal C/EBPβ levels increase upon aminoacid deprivation (Grewal et al 2009) …”
Section: Studies On Neuronsmentioning
confidence: 94%
“…Some examples are provided below but the list cannot be exhaustive. Various genes involved in neurotransmission are C/EBPβ targets including neurotransmitter synthesis enzymes such as choline acetyltransferase (Robert et al 2002) or histidine decarboxylase (Cortes-Canteli et al 2004), neurotransmitter precursors such as preprotachykinin-A (Kovacs et al 2006) or the aminoacid transporter SNAT2 which is used by neurons to take up Gln when in need of increased Glu synthesis (Grewal et al 2009). C/EBPβ targets also include neurotransmitter receptors such as metabotropic glutamate receptor 1 (Crepaldi et al 2007) or the pain-related purinergic receptor P2X3 (Ugarte et al 2012), ion channels like TRPV1 (Ugarte et al 2013) or proteins involved in receptor and ion channel trafficking like sorting nexin 27 (Wang et al 2013b).…”
Section: Regulation Of Specific/key Neuronal Genes By C/ebpβ and C/ebpδmentioning
confidence: 98%
“…This process is essential for recycling the neurotransmitter glutamate (13). However, the exact contribution of SNAT2 to the glutamate-glutamine cycle is still controversially discussed (14).…”
mentioning
confidence: 99%